Experiential and External Factors Influencing Discontinuance of the Diploy Digital Talent Pool Platform - Marco Alfan Sumarto; Teguh Raharjo (Green Publisher Indonesia, 2026)
The digital transformation has driven the emergence of digital talent pool systems such as Diploy, developed by Indonesia's Ministry of Communication and Digital Affairs to bridge Digital Talent Scholarship (DTS) graduates with industry demand. However, evaluation has become urgent because the platform shows very low effectiveness; only about 1% of DTS graduates have been successfully recruited through Diploy. This indicates a substantial gap between the platform's strategic goals and its actual performance. Before designing appropriate improvement strategies, it is crucial to understand the factors that drive employer partners to discontinue using Diploy. This study aims to analyze the key factors influencing discontinuance decisions, focusing on two dimensions: experiential and external factors. Using a quantitative approach, the study applies Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that poor system quality has a statistically significant effect on platform discontinuance (p = 0.015), underscoring the importance of technical reliability in retaining users. Other variables, such as information quality, service quality, talent mismatch, and trust, do not exhibit statistically significant influence. This insignificance may stem from varied user experiences and a lower perceived urgency compared with the immediate impact of technical issues on recruitment. Therefore, improving system performance should be prioritized, alongside long-term efforts to enhance platform credibility and talent fit.